The Level Of Trust Of Islamic Bank Customers After The Implementation Of The Dormant Account Freezing Policy - Liana Dewi; Revalina Yunijar; Via Fitriani (Jurnal Ekonomi Bisnis dan Manajemen, 2026)
The implementation of the dormant account freezing policy by the Financial Transaction Reports and Analysis Center (PPATK) in mid-2025 has attracted public attention. This incident has negatively impacted banking customer trust. This study aims to analyze customer responses to the implementation of the dormant account freezing policy by PPATK on the level of trust of Islamic bank customers. In addition to analyzing the relationship between customer responses and trust in Islamic banks, this study also analyzes the appropriateness of the dormant account freezing implementation from the perspective of customer protection regulations and PPATK's authority. Quantitative methods were used to analyze the relationship between Islamic bank customer responses and the level of customer trust in Islamic banks after the policy was implemented. Research data were collected through a questionnaire developed based on its suitability with stakeholder theory. In an effort to analyze the appropriateness of the policy implementation from a regulatory perspective, the regulatory basis applicable in Indonesia was used. The sample in this study was 270 Islamic bank customers in Tasikmalaya City. The results of the study suggest a positive relationship between public response to the dormant account freezing policy and the level of customer trust in Islamic banks. Based on the regulatory analysis, it was found that Islamic banks are obliged to provide a sense of security for customers related to the transparency of Islamic bank products and services. However, based on the law, the PPATK's duties in monitoring suspicious transactions are considered to exceed its limits and authority.